Freedom of religious organizations - Norton, Jane Calderwood (Oxford : Oxford University Press, 2016)
An analysis of the interaction between religious organisations and the law, this book will examine how English law applies to religious organisations where there are conflicts between the organisation and the law.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 5, 2016).
Keywords: Religion and law -- England; Religious law and legislation -- England; Ecclesiastical law -- England; Law; Laws of specific jurisdictions & specific areas of law